2011
DOI: 10.1103/physrevb.84.184404
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved imaging of magnetoelectric switching in multiferroic MnWO4

Abstract: We show that the electric-field-induced reversal of the magnetic order parameter in multiferroic MnWO 4 occurs on the time scale of milliseconds. Throughout the switching process the magnetic order and the magnetically induced electric polarization remain rigidly coupled. The temporal progression of the domain structure was imaged with nanosecond resolution by an electrical-pump-optical-probe technique using optical second harmonic generation. These nonequilibrium domain states significantly differ from the qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 27 publications
4
39
1
Order By: Relevance
“…The steep increase of ν 0 in the vicinity of T N 2 denotes the softening of the switching process in the vicinity of the continuous multiferroic phase transition. However, away from the second order multiferroic phase transition, the switching time for stimulating fields of 1 kV/mm lies in the millisecond range, which is relatively slow compared to canonical ferroelectrics (e.g., 34,39 ), but is in accordance with reports on such slow switching in MnWO 4 obtained in time domain studies 17,18 . The effective switching rate forms a minimum and slightly re-increases on approaching T N 1 , as already implied by the P sw (T ) data discussed above.…”
Section: Domain Dynamics In the Multiferroic Phasesupporting
confidence: 89%
See 2 more Smart Citations
“…The steep increase of ν 0 in the vicinity of T N 2 denotes the softening of the switching process in the vicinity of the continuous multiferroic phase transition. However, away from the second order multiferroic phase transition, the switching time for stimulating fields of 1 kV/mm lies in the millisecond range, which is relatively slow compared to canonical ferroelectrics (e.g., 34,39 ), but is in accordance with reports on such slow switching in MnWO 4 obtained in time domain studies 17,18 . The effective switching rate forms a minimum and slightly re-increases on approaching T N 1 , as already implied by the P sw (T ) data discussed above.…”
Section: Domain Dynamics In the Multiferroic Phasesupporting
confidence: 89%
“…Even though the dimensional meaning of this number should not be overemphasized it is in accord with the reduced dimensionality observed via the direct SHGimaging of the domains, which have the shape of elongated bubbles and show one-dimensional growth 16 . A small orientational preference with respect to the magnetic easy-axis and a shape dependence on the electric poling history was observed 16,17 . The domains are large objects with extension above µm and for the preferred direction even up to mm, i.e.…”
Section: Domain Dynamics In the Multiferroic Phasementioning
confidence: 95%
See 1 more Smart Citation
“…Phenomenologically it has been demonstrated that a reorientation by acting on the improper (electric) order parameter tends to be slow with reversal times in the millisecond range 38,39 . By acting on the primary (magnetic) order parameter, theory predicts scenarios with a reversal within a few picoseconds, yet at so far unrealistically large fields 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In multiferroics the problem of fast switching is not fully settled. Due to low static electric polarization in spin-driven multiferroics [6,27] substantial degradation of the switching time has been reported [28]. Extremely short switching times of electric polarization and of magnetization can be reached using pulsed laser light.…”
mentioning
confidence: 99%